2018
DOI: 10.1080/0158037x.2018.1497592
|View full text |Cite|
|
Sign up to set email alerts
|

Learning the (hidden) silence policy within the police

Abstract: Many organisations declare that the ability for employees to speak out about organisational matters is important for organisational development. However, recent literature reports a widespread fear of retaliation among employees if they express themselvesespecially within the police. The point of departure of the present article is the tension and discrepancy between official policy and officers' accounts of the conversational climate within the police. Through empirical examples from data consisting of field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 22 publications
(22 reference statements)
1
18
0
Order By: Relevance
“…Loftus (2009) labelled such safe places 'white spaces', looking at how in them derogatory and even directly racist police talk can be openly expressed, sustaining unequal power relations both among police employees themselves and in police encounters with minorities. In previous research, I have developed the understanding of the concepts 'safe places' and 'white spaces', bringing into relief the significance of the conditions of language used within different areas in the police (Wieslander 2014(Wieslander , 2018(Wieslander , 2019, see also Sefton 2011). I have used the term 'safe (discursive) spaces' to point at these spaces as contextualized and regulated beyond only race, and shown that language and humour are conditioned differently in relation to different people, groups, times, locations and occasions.…”
Section: Humour In Police Culturementioning
confidence: 99%
See 4 more Smart Citations
“…Loftus (2009) labelled such safe places 'white spaces', looking at how in them derogatory and even directly racist police talk can be openly expressed, sustaining unequal power relations both among police employees themselves and in police encounters with minorities. In previous research, I have developed the understanding of the concepts 'safe places' and 'white spaces', bringing into relief the significance of the conditions of language used within different areas in the police (Wieslander 2014(Wieslander , 2018(Wieslander , 2019, see also Sefton 2011). I have used the term 'safe (discursive) spaces' to point at these spaces as contextualized and regulated beyond only race, and shown that language and humour are conditioned differently in relation to different people, groups, times, locations and occasions.…”
Section: Humour In Police Culturementioning
confidence: 99%
“…This form of routine resistance to the managerial discourse on freedom of speech constituted not only a counter-discourse of a suppressive conversational climate, but also characterized the management as sneaky, giving reprisals to the employees while proclaiming freedom of speech. The cynical punchlines served to inform other peers and me about the perceived working conditions, and thus also constituted a truth very few dared to challenge (see Wieslander 2018).…”
Section: At the Stations: Resisting Managerial Messagesmentioning
confidence: 99%
See 3 more Smart Citations